Radioactive Iodine for the Treatment of Subclinical Thyrotoxicosis Grade 1 and 2: Outcome of up to 18-Year Follow Up - Phowira, Jason; Coffey, Katherine L.; Bartholomew, Peter H.; Vennart, Nicholas; Moreira, Matheus; Emerson, Hannah; Kennedy, David; Weaver, Jolanta U. (Frontiers in Endocrinology, 2022)
Background: Subclinical thyrotoxicosis (SCT) is associated with significant morbidity and mortality, specifically increased risk of atrial fibrillation and cardiovascular death. The management is ill-defined due to the scarcity of randomised controlled studies. Some clinicians recommend radioiodine (RAI) treatment however its long-term outcome is unknown. Therefore, further data is needed to provide robust evidence-based guidelines. Methods: A prospective, single-protocol analysis of the outcome of SCT patients (Grade 1; 0.1-0.4 mIU/L and Grade 2; <0.1 mIU/L) treated with mean dose of 427 MBq of I131, followed up for up to 18 years. Thyroid function tests were measured at 4-6 weeks, 3-, 6-, and 12-months post-RAI, and annually thereafter. Cure was defined as achieving a euthyroid/hypothyroid state. Results: Seventy-eight patients with a median age of 68 years (range 36-84) and varying aetiology [55 toxic multinodular goitre (TMNG), 10 toxic nodule (TN) and 13 Graves’ disease (GD)] were followed up for a median period of 7.5 years (range 1-18). The cure rate was 100%. The rates of hypothyroidism in TMNG, TN and GD were 23.6%, 30% and 38.5% respectively. The median time to hypothyroidism was 6 and 12 months in GD and TMNG/TN respectively. No differences in outcome between Grade 1 versus Grade 2 were observed. Conclusion: RAI using single mean dose of 427 MBq is effective and safe, irrespective of aetiology or grade of TSH suppression. GD patients become hypothyroid within the first year, whilst TMNG/TN for up to 9-years. Thus after 12 months of follow up, annual thyroid function monitoring is advised.